Smart composites : mechanics and design - Elhajjar, Rani; La Saponara, Valeria, 1970-; Muliana, Anastasia (Composite materials (CRC Press), 2013)
"Preface Smart composites as we now know them are increasingly a key factor in scientific and technological achievement of materials. Recent advances in design and optimization of composite structures have played a significant role in the current development of smart materials and structures. Working with these materials requires going beyond mechanics focused on only the structural level response. Researchers and engineers find themselves needing to have an interdisciplinary knowledge to understand, predict, and model the properties of these materials that have unique structural, processing, and sensing abilities. The new generation of smart materials will consist of various chemical components and microstructural morphologies but may also respond differently under combined external influence. The ability to then combine mechanical, thermal, electromagnetic, and other responses becomes critical not only at the material level but also at the structural scale. The materials are not only expected to bear mechanical loadings but also are designed with inherent capability lending itself for structural health monitoring or nondestructive sensing capabilities. At the same time, these new technologies have to support one another in a symbiotic way. With this book, we have attempted to present a selection of the latest information in the field of smart materials. In the first section of the book, we discuss topics in smart materials related to electrically conductive, magnetostrictive nanocomposites and design of active fiber composites"--